EFFECTIVENESS OF THE USE OF DIGITAL TECHNOLOGIES IN PHILOLOGY EDUCATION (Ustozlar uchun, 2026)
This article analyzes the pedagogical and didactic effectiveness of the use of digital technologies in philology education. The impact of digital learning tools, including electronic textbooks, online learning platforms, interactive programs and multimedia resources on the process of teaching language and literature is highlighted. The study substantiates that digital technologies are an important factor in developing students' speech competence, independent learning skills and analytical thinking. It also shows the possibilities of improving the quality and efficiency of education through the use of modern information and communication technologies in philology education.